Experimental and numerical study on scratching test - Öpöz, Tahsin; Chen, Xun (Cranfield University Press, 2013)
This paper presents recent investigation of the material removal mechanism in single grit grinding test. Single grit scratches were generated experimentally by using CBN grit on En24T steel and compared with numerical simulation by using finite element modelling (FEM). The material removal mechanism was observed along the scratch length to understand the effectiveness of ploughing and cutting mechanism throughout the scratch. Experiments showed that cutting is efficient at first half of the scratch while ploughing is significantly higher at the second half of the scratch. At the exit side of the scratch almost no material removal takes place. It has demonstrated that FEM simulations match well with experimental results.
Keywords: single grit scratch; ploughing; cutting